Unlocking Supply Chain Excellence through Delivery Prioritization : Membuka Keunggulan Rantai Pasokan melalui Prioritas Pengiriman - Devany Arsi Ramadhan; Hana Catur Wahyuni (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates supply chain performance prioritization and improvement strategies for PT. XYZ, a starter card distributor facing operational challenges. Utilizing SCOR and F-AHP methodologies, the research identifies delivery as the highest priority criterion for enhancement, with a weight of 0.49. Recommendations include refining delivery systems, engaging customer feedback, and implementing software solutions to minimize inconsistencies. These findings offer valuable insights into supply chain management for similar distributors, aiming to enhance efficiency, customer satisfaction, and market competitiveness. Highlight: SCOR and F-AHP used for supply chain evaluation. Delivery prioritized for optimization, key to customer satisfaction. Recommendations: refine systems, engage feedback, implement software for consistency. Keyword: Supply Chain Management, SCOR, F-AHP, Performance Prioritization, Delivery Optimization